ANALYSIS OF THE COMPLIANCE OF SHOPEE PAYLATER WITH ISLAMIC ECONOMIC PRINCIPLES IN DIGITAL CREDIT PRACTICES - Nabilah Auliya Cahyaningtias; Gheriya Aufa Huwaida; Alya Rahmadina; Budi Jaya Putra (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
This study aims to analyze the compliance of the Shopee PayLater service with Islamic economic principles in digital credit practices. Shopee PayLater is a form of Buy Now Pay Later (BNPL) service that offers payment convenience to the public. The financing volume reached IDR 62.17 trillion as of March 2024. This research employs a qualitative approach with descriptive methods and literature studies. The findings reveal that the Shopee PayLater system does not fully align with sharia principles due to the presence of riba, applied through a fixed interest rate of 2.95% and a late payment penalty of 5%, as well as the absence of a clear contract (akad), indicating elements of gharar. Moreover, this service negatively impacts users' consumptive behavior, especially among university students, and diverts from the objectives of maqashid shariah, such as preserving wealth (hifz al-mal) and intellect (hifz al-‘aql). Therefore, a transformation of the PayLater digital financial system is needed toward a sharia-compliant model with clear contractual terms and free from interest.